Lived experiences of out-of-wedlock adolescent pregnancy: a phenomenological study of respectful maternity care in Bengkulu - Poppy Siska Putri; Nurul Maulani (Universitas Aisyiyah Yogyakarta, 2026)
Adolescent pregnancy is a complex phenomenon influenced not only by medical factors but also by social, cultural, and psychological determinants. This study aimed to explore adolescents’ experiences of pregnancy within cultural contexts and their relationship with the implementation of Respectful Maternity Care (RMC) principles in Seluma Regency, Bengkulu. A qualitative phenomenological approach was employed, with data collected through in-depth interviews with 10 pregnant adolescents as primary participants and 8 supporting informants, including family members, healthcare providers, religious leaders, and community figures, selected through purposive and snowball sampling techniques. Data were analyzed thematically. Four main themes emerged: socio-cultural constructions of adolescent pregnancy, family acceptance and support dynamics, socio-cultural implications for healthcare access, and healthcare experiences from the RMC perspective. Findings indicate that social stigma and cultural norms create emotional pressure and influence healthcare utilization. Family support plays a critical role in shaping adolescents’ experiences, including decision-making processes. Self-acceptance and adaptive coping mechanisms contribute to psychological resilience, while the quality of communication and treatment by healthcare providers affects comfort and confidence in accessing health services. In conclusion, adolescent pregnancy experiences are shaped by interactions among socio-cultural, familial, psychological, and healthcare factors. The implementation of adolescent-centered, communicative, and non-discriminatory care in line with RMC principles is essential to improve both access to and the quality of healthcare services for pregnant adolescents.